TOPICAL ISSUES OF CRIMINAL LIABILITY FOR UNLAWFUL DEPRIVATION OF LIBERTY OR ABDUCTION OF A PERSON (ARTICLE 146 OF THE CRIMINAL CODE OF UKRAINE) - Lykhova, Sofiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: criminal law characteristics of the legal elements of the crime provided for in the disposition of Article 146 of the Criminal Code of Ukraine. Methods: the study was conducted using a dialectical approach, methods of analysis, synthesis, as well as a number of general scientific and special legal research methods. Results: the author comes to the conclusion that Article 146 of the Criminal Code of Ukraine provides for criminal liability for a crime committed in two forms: illegal deprivation of liberty and kidnapping. And although their legal elements are provided for in the dispositions of the same article and they are the same in terms of the degree of public danger, each of these forms of crime has its own characteristics and certain qualifying features may be applied only to one of these two forms. The peculiarity of this crime is that its composition is formal, and the crime itself is ongoing. Although in some cases, the moment of the beginning and end of the crime coincide in time. Particular attention is paid to the study of the content of aggravating features provided for in Parts 2 and 3 of Article 146 of the Criminal Code of Ukraine. Discussion: the wording of the qualifying features of the legal elements of the crime provided for in the disposition of Article 146 of the CC of Ukraine was made in violation of the logic of the legislative perception of their real meaning and purpose: "method dangerous to the life or health of the victim", "causing physical suffering to the victim", "use of weapons". Even without going into details, one can see the existence of dissonance in their coexistence from the perspective of the ratio of their volume and content, since it is obvious that they are overlapping, that some features are reproduced by others.